(untitled) (Journal of Informatics Education and Research, 2025)
GST is an indirect tax levied on goods and services sold in India. It replaced many indirect taxes such as excise duty, VAT (value added tax), services tax, etc. The Goods and Service Tax Act was passed in the Parliament on 29th March 2017 and came into effect on 1st July 2017." The introduction of GST in India would be the country’s biggest tax reform to date. As a result, the definition of the goods and services tax (GST) as a consumption-based tax derived from the manufacture, sale, and consumption of products and services further contributes to the process of turning the nation into a single, integrated common market. Primary data has been gathered for the study from questionnaire from retailers through convenient sampling. This study examines the complex terrain of the Goods and Services Tax (GST) to evaluate its dramatic effects on the business and economic ecologies while also examining the level of awareness and impact on various factors of GST among various retailers. GST was enacted as a revolutionary tax reform in many nations and has been the focus of intense scrutiny and debate. This study focuses and analyses the effects of the GST and the corresponding levels of awareness among different types of retailers.